Reproduction naturelle de Crassostrea gigas Thunberg dans le bassin de Marennes-Oleron en 1979 et 1981: Aspects biochimiques et energetiques. - Deslous-paoli, Jean-marc; Heral, Maurice; Berthome, Jean-paul; Razet, Daniel; Garnier, Jacqueline (ISTPM, 1981)
In summer 1979, the natural reproduction of oysters Crassostrea gigas Thunberg, in Marennes-Oleron basin, produced a large number of juveniles which was not the case in summer 1981. If one compares the evolution of the main constituents of the flesh, one can see that, at the beginning of August, before spawning the male oysters in 1981 contained 6,3% less proteins, 34,2% less lipids and 61,2% less glucids than those in 1979 and respectively 12,3%, 21,3% and 69,8% less as far as females are concerned. The energetic value of ash-free dry flesh of female oysters is nearly the same for the two years whereas for male oysters the value is slightly lower in 1981 than in 1979. The total energetic values of male and female oysters show a slight difference between 1981 and 1979 as do their chemical constituents. A significant delay in gametogenesis was also seen for 1981 oysters compared to 1979. This delay in gonads maturation may be due first to a lack of potential phytoplanktonic and detritic food in spring 1981 compared to 1979, this does not allow the accumulation of glycogen stocks which are necessary to the formation of gametes. The delay is also the consequence of a too low temperature in the end of the gametogenesis. Lors de l'été 1979, la reproduction naturelle des huîtres Crassostrea gigas Thunberg, cultivées dans le bassin de Marennes-Oléron permit une récolte importante de juvéniles, ce qui ne fut pas le cas durant l'été 1981. La comparaison de l'évolution des principaux constituants de la chair montre qu'au début du mois d'août, soit avant la ponte, les huîtres de 1981 présentent un déficit, par rapport à celles de 1979, de 6,3 % en protéines, 34,2 % en lipides et 61,2 % en glucides pour les mâles, et, respectivement de 12,3%;, 2 1 , 3% et 6 9 , 8% pour les femelles. La teneur énergétique relative de la chair sèche sans cendre des huîtres femelles est sensiblement identique pendant ces deux années, alors que pour les huîtres mâles cette teneur est légèrement plus faible en 1981 qu'en 1979. Comme pour les ...